Device for modeling of intra-arterial circulation: application in experimental cardiology. (14th October 2021) - Germanova, O; Germanov, V A; Shchukin, Y V; Germanov, A V; Galati, G
Abstract: Purpose of study: Using an original device for modeling of intra-arterial blood circulation, to study the features of intravascular hemodynamics with a regular heart rhythm and with various rhythm disturbances. Material and methods: We used an original device developed by us to simulate intra-arterial circulation (Document of invention No. RU 202780 U1). The main part of the device is a glass tube of a rotameter with a length of 365 mm, an inlet end with a diameter of 20 mm, an outlet end of 16.5 mm, which is a model of an arterial vessel. Flexible silicone tubes are attached to the rotameter on both sides, with free ends connected to an electric pump, with various modes of operation (imitation of pulse waves with regular rhythm, premature ventricular contractions (PVCs), atrial fibrillation (AF). An aqueous solution of glycerin was introduced into a closed system diluted with water corresponding to the viscosity of the blood. A 5 mm long silk thread was alternately installed inside the tube, an intravascular piezoelectric crystal pressure probe connected to an oscilloscope. Also it was injected inside the tube a dye - clerical ink. Results: With electric pump, we simulated the spreading of the pulse wave in regular heart rate, PVCs and AF. We observed the effect of a pressure wave (deflection of a silk thread, the appearance of a turbulent flow when using a dye) on the walls of the rotameter, with the formation of standing, reflected waves during the PVCs and AF. The pressure probe registered an increase in pressure inside the tube during the spread of the 1st post-extrasystolic contraction wave up to 58%, the wave after a long pause of more than 2 seconds with AF by 44% compared to the regular rhythm. Conclusion: A device for modeling of intra-arterial circulation allows a wide range of experimental work in cardiology, normal and pathological physiology, and biophysics. Funding Acknowledgement: Type of funding sources: None.